2013
DOI: 10.1128/jb.02037-12
|View full text |Cite
|
Sign up to set email alerts
|

Archaeal DNA Polymerase D but Not DNA Polymerase B Is Required for Genome Replication in Thermococcus kodakarensis

Abstract: c Three evolutionarily distinct families of replicative DNA polymerases, designated polymerase B (Pol B), Pol C, and Pol D, have been identified. Members of the Pol B family are present in all three domains of life, whereas Pol C exists only in Bacteria and Pol D exists only in Archaea. Pol B enzymes replicate eukaryotic chromosomal DNA, and as members of the Pol B family are present in all Archaea, it has been assumed that Pol B enzymes also replicate archaeal genomes. Here we report the construction of Therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
72
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(77 citation statements)
references
References 53 publications
5
72
0
Order By: Relevance
“…The profile of frameshifts, tandem duplications, and larger deletion and BPSs obtained in this work was generated from molecular analysis of the apt locus from over 200 6-MP r strains. We found that the mutation profile is comparable to that of T. kodakarensis, also assayed by 6-MP counterselection with an hpt gene (49). Interestingly, a 5-FOAbased forward mutation assay in S. acidocaldarius revealed that frameshift mutations are dominant in this organism (50).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…The profile of frameshifts, tandem duplications, and larger deletion and BPSs obtained in this work was generated from molecular analysis of the apt locus from over 200 6-MP r strains. We found that the mutation profile is comparable to that of T. kodakarensis, also assayed by 6-MP counterselection with an hpt gene (49). Interestingly, a 5-FOAbased forward mutation assay in S. acidocaldarius revealed that frameshift mutations are dominant in this organism (50).…”
Section: Discussionmentioning
confidence: 62%
“…Interestingly, a 5-FOAbased forward mutation assay in S. acidocaldarius revealed that frameshift mutations are dominant in this organism (50). Furthermore, this and a few other studies have revealed that the transitions outnumbered transversions by more than 2-fold, and a very strong strand bias for G or C-to-A or T transitions was observed (49,50,52,53). These should be further studied by generating mutants deficient in certain DNA repair mechanisms and investigating their effect on the profile of spontaneous mutations.…”
Section: Discussionmentioning
confidence: 99%
“…This would make archaeal organisms similar to eukaryotic organisms, in which Polε replicates the leading strand while Polδ replicates the lagging strand. Using gene knockouts, however, it was found that, at least in some species, PolB is not required for cell viability (Cubonova et al, 2013;Sarmiento et al, 2013). These results suggest that only PolD is the replicative enzyme in those species.…”
Section: The Genetics Eramentioning
confidence: 80%
“…A helical interdomain insertion is green. Other motifs are colored as follows: the uracil-binding motif is red, the "DIE" in the Exo I motif is green, residue D215 in the Exo II motif is white gray, residue D315 in the Exo III motif is yellow, the "YxGG" motif is white gray, the Motif A is green, the Motif B is blue and the Motif C is magenta for genome replication in T. kodakarensis (Cubonova et al 2013). Although biochemical data suggested that pol Ds from P. furiosus and P. abyssi were suitable enzymes for PCR (Killelea et al 2014), these DNA pols have not been commercialized so far.…”
Section: Introductionmentioning
confidence: 99%